Strong Field-Induced Frequency Conversion of Laser Radiation in Plasma Plumes: Recent Achievements - R. A. Ganeev (The Scientific World Journal)
New findings in plasma harmonics studies using strong laser fields are reviewed. We discuss recent achievements in the growth of the efficiency of coherent extreme ultraviolet (XUV) radiation sources based on frequency conversion of the ultrashort pulses in the laser-produced plasmas, which allowed for the spectral and structural studies of matter through the high-order harmonic generation (HHG) spectroscopy. These studies showed that plasma HHG can open new opportunities in many unexpected areas of laser-matter interaction. Besides being considered as an alternative method for generation of coherent XUV radiation, it can be used as a powerful tool for various spectroscopic and analytical applications.